The Influence of Product Quality and Promotion on Repurchase Intent, with Customer Satisfaction as the Mediating Variable: (A Study on Kemejaberkah.2nd Online Shop Consumers) - Amar, Amar; Mochtoha, Himawan (Politeknik Negeri Batam, 2025)
This study investigates the role of customer satisfaction as an intervening variable in analyzing the impact of product quality and marketing on repurchase intention among customers of Kemejaberkah.2nd online shop. A quantitative research method with a descriptive approach was employed. Data were collected through a questionnaire distributed to 115 individuals who had made at least three repeat purchases in 2023. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results revealed that both product quality and promotion have a positive and significant effect on customer satisfaction and repurchase intention. Moreover, customer satisfaction mediates the relationship between product quality and promotion with repurchase intention. These findings highlight the importance of developing strategies that improve product quality and marketing effectiveness to sustain customer satisfaction. By applying the right approach, businesses can enhance customer satisfaction and drive repeat purchases.